2019
DOI: 10.21203/rs.2.10499/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence of Lower Urinary Tract Symptoms Based on Individual and Clinical Parameters in Patients with Multiple Sclerosis

Abstract: Background: Most patients with multiple sclerosis (MS) suffer from bladder dysfunction during the

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the past 2 decades, several studies have investigated the prevalence of UI and FI in individuals diagnosed with MS [5-16]. For example, a US cross-sectional survey study including 1,047 participants with MS revealed that around 79% of the sample had some type of UI [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 2 decades, several studies have investigated the prevalence of UI and FI in individuals diagnosed with MS [5-16]. For example, a US cross-sectional survey study including 1,047 participants with MS revealed that around 79% of the sample had some type of UI [9].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has examined in the past 20 years the association between MS and both urinary (UI) and fecal incontinence (FI) [5-16]. For example, a study of 73 adults with MS from Australia revealed that approximately 31% of the sample reported occasional to daily UI, while the proportion of participants with frequent FI was around 14% [6].…”
Section: Introductionmentioning
confidence: 99%